Back Cover: Helical Molecular Springs with Varying Spring Constants (Angew. Chem. Int. Ed. 50/2022). Issue 50 (22nd November 2022) - Murphy, Kyle E.; McKay, Kyle T.; Schenkelberg, Mica; Sharafi, Mona; Vestrheim, Olav; Ivancic, Monika; Li, Jianing; Schneebeli, Severin T.
Abstract : Helical molecular springs built from chiral ladder polymers expand and contract without unfolding at room temperature. In their Communication (e202209772), Severin T. Schneebeli and co‐workers show that in solution such helical ladder polymers can act like classical Hookean springs with adjustable spring constants.